Resin-modified glass ionomer containing calcium glycerophosphate: Physico-mechanical properties and enamel demineralization - Santos, Sâmia Sass [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Moraes, João Carlos Silos [UNESP]; Souza, José Antônio Santos [UNESP]; Oliveira, Lenara Queiroz Chaves [UNESP]; Pedrini, Denise [UNESP] (FapUNIFESP (SciELO), 2019)
Sources of calcium and phosphate have been added to dental restorative materials to improve their anticaries effect. Objective: This study evaluated the effect of adding calcium glycerophosphate (CaGP) to resin-modified glass ionomer cement (RMGIC) on the physico-mechanical properties, ion release, and enamel demineralization. Material and Methods: Specimens were fabricated for each experimental group: RMGIC without CaGP (Control), RMGIC with 1, 3 and 9% CaGP. To determine the release of fluoride (F), calcium (Ca) and phosphorus (P), six specimens were immersed in demineralization and remineralization solutions for 15 days. In another experimental trial, the following physico-mechanical properties were evaluated at time intervals of 1 and 7 days after fabrication: compressive strength (n=12), diametral tensile strength (n=12), surface hardness of material (n=6) and the degree of conversion of monomers (n=8). To study enamel demineralization, specimens (n=12) were attached to enamel blocks and submitted to pH-cycling. Subsequently, surface and cross-sectional hardness and the concentration of F, Ca and P in enamel were determined. Results: The addition of CaGP to RMGIC led to higher mean release of F, Ca and P when compared with control (p<0.001). Mechanical properties were within the range of those of the ionomer cements after addition of 1% and 3% CaGP. The degree of conversion did not differ between groups at the 1st and the 7th day (p>0.439). The addition of 3% and 9% CaGP reduced mineral loss and increased F, Ca and P in the enamel when compared with control (p<0.05). Conclusion: The addition of 3% CaGP in RMGIC increased the release of F, P and Ca, reduced enamel demineralization, and maintained the physico-mechanical properties within the parameters for this material.
Keywords: Compressive strength; Glass ionomer cements; Phosphates; Polymerization; Tooth demineralization